ANALISIS NILAI PASAR WAJAR SAHAM PT TOBA BARA SEJAHTRA DALAM RANGKA INITIAL PUBLIC OFFERING (IPO) DENGAN MENGGUNAKAN PENDEKATAN DCF DAN RELATIVE VALUATION - , Amanda Indriasari; , Dr. Mamduh M. Hanafi, M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Initial Public Offering (IPO) or the first sale of stock by a company to the public is one of several alternatives that can be taken by a company's management to raise fund for additional capital requirements or for meeting liquidity needs of the owners. On the average, the pricing of an IPO is underpriced or below its market value (intrinsic value) and this phenomenon is known as IPO Underpricing. One of other causes that might affect the pricing of a stock is the condition of the industry where a company operates in. For example, coal mining industry has been affected by falling coal prices that has happened since the fourth quarter of 2011. Prices have been falling globally and locally due to a slowdown in use from China - as a result of declining orders from nations in Europe which had been hit by global crisis. PT Toba Bara Sejahtra as the object of this research is also a coal mining company and underwent an IPO in July 2012. The research aimed to analyze the fair market value of PT Toba Bara Sejahtra's stock as of December 2011 to be compared to the offering stock price when the Company was undergoing an IPO in July 2012, in order to obtain information whether overvaluation or undervaluation exists. Audited financial statements of PTToba Bara Sejahtra for the year 2009 until 2011 is one of data sources used in this research. Value analysis by using relative valuation or market approach is implemented by seeking other similar companies in the same industry, then selecting multiples used to convert equity book value of the appraised company into market value. Multiples used in the relative valuation are PER (Price/Earning Ratio), P/S (Price/Sales Ratio), and PBV (Price to Book Value). The use of income approach to analyze the market value is applied by using discounted cash flow (DCF) method with these following steps: analyzing and forecasting the revenues, fo recasting net income, forecasting free cash flow, determining discount rate and estimating the value. Scenario analysis is used in forecasting revenues. There are three scenarios: optimistic scenario, neutral scenario, and pessimistic scenario and each scenario has the same probability. The result of relative valuation method is Rp3.220 per share. The results of three scenarios in DCF method - optimistic, neutral and pessimistic - are Rp3.594, Rp3.101, and Rp2.774 per share respectively. Having the same probability for each scenario, the result of DCF method is Rp3.156 per share. The estimated fair market value of PT Toba Bara Sejahtra's stock as of December 31, 2011, calculated by value reconciliation - by weighting each method - is Rp3.182 per share. The stock price during IPO on July 6, 2012 is Rp1.900. If this is compared to the estimated fair market value, the stock of PT Toba Bara Sejahtra is undervalued.